THE EFFECT OF SCIENCE TECHNOLOGY AND SOCIETY MODELS ON SCIENCE PROCESS SKILLS - Agatha Asih Nugraheni; Wuri Wuryandani (Universitas Negeri Yogyakarta, 2018)
This study aims to integrate the Science Technology and Society models on the students' processes in grade IV elementary school. The implementation of this study uses a quantitative approach with a type of quasi-experimental research. The population of the study sample was calculated from the second class, namely the fourth grade of SD Negeri Margoagung as the experimental class and class IV SD Ngino 1 as the control class. Data analysis is an independent sample t-test. The results showed that there was a significant influence of the Science and Community Technology model on the process skills of the fourth grade students of Seyegan Margoagung Group with a value of 0.751 and p 0.000 0.05. The Science Technology Model and the Unused Community. The Science Technology Model and Sociality are significant and positive in terms of process skills and student participation. This learning model can be applied to classes that can improve the process and involvement of students, students are easier to receive the material delivered by the teacher.PENGARUH MODEL SCIENCE TECHNOLOGY AND SOCIETY TERHADAP KETERAMPILAN PROSES SAINS Penelitian ini bertujuan untuk menguji pengaruh model Science Technology and Society terhadap keterampilan proses sains siswa pada kelas IV SD. Pelaksanaan penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian quasi eksperimen. Populasi sampel penelitian yang digunakan diambil dari dua kelas yaitu kelas IV SD Negeri Margoagung sebagai kelas eksperimen dan kelas IV SD Ngino 1 sebagai kelas kontrol. Analisis data yang digunakan adalah independent sampel t-test. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan model Science Technology and Society terhadap keterampilan proses sains siswa kelas IV SD seGugus Margoagung Seyegan dengan nilai thitung 0,751 dan p 0,000 0,05. Model Science Technology and Society berpengaruh terhadap keterampilan proses sains siswa. Model Science Technology and Sociaety berpengaruh secara signifikan dan positif ditinjau dari keterampilan proses sains dan partisipasi siswa. Model pembelajaran ini dapat diterapkan pada suatu kelas dapat meningkatkan keterampilan proses sains dan partisipasi siswa, sehingga siswa lebih mudah dalam menerima materi yang disampaikan oleh guru.